Pengaruh Pemberian Sari Kurma dalam Manajemen Aktif Kala III Di Puskesmas Bara - Baraya Makassar - Uliarta Marbun; Irnawati Irnawati; Lili Purnama Sari; Dahniar Dahniar (Jurnal Sehat Mandiri, 2025)
Childbirth is the process of delivering a fetus, which requires stamina and optimal physical condition due to the increased metabolism during the process. The muscle activity during pushing requires optimal energy, which can be obtained from proper nutrition and hydration. This study aims to determine the effect of date syrup administration in the active management of the third stage of labor at Bara-Barayya Health Center. The study used a quasi-experimental design with a pre-test and post-test with a control group. The population for this study was multiparous women (parity 2-4) who gave birth at Bara-Barayya Health Center between April and June 2023, with a sample taken through accidental sampling. Data was collected through direct observation using an observation sheet to assess the duration of the third stage of labor. Data analysis was conducted using an independent T-test. The results showed a p-value of 0.005 < 0.05, indicating that date syrup administration has an effect on the active management of the third stage of labor at Bara-Barayya Health Center in 2023. The conclusion is that date syrup administration influences the active management of the third stage of labor. This study recommends that Bara-Barayya Health Center and the Midwife Team educate pregnant women to consume date syrup starting from the third trimester to shorten labor duration and reduce pain.